Occupational and living condition of artisanal fishermen in Brgy. Igcadlum, San Joaquin, Iloilo. - Jacaban, Sharon Rose F.
This is a study about the occupational and living condition of artisanal fishermen in a rural fishing community. This is a descriptive study which aims to ascertain the socio-demographic profile of the artisanal fishermen and the fishing households, the fishing gears and the craft presently use, their living condition, and their perception of their present and future household condition., The respondents are household heads. There was a total of 21 respondents who were chosen using systematic random sampling. The researchers used an interview schedule in obtaining data. The results of the study show that artisanal fishermen are in their 40s, have low educational attainment and adopt the same means of living as their parents. They have large household size and most of their household members are unemployed. Majority of the artisanal fishermen employs traditional fishing gears and craft, which lead to having poor catch which most of teh time, just enough for their family's consumption. This in effect leads to having poor dwelling units made of bamboo and nipa thatched. Most of them have low aspiration of their present and future condition.